Nature management history and prospects for improving environmental monitoring in Galapagos Islands (Republic of Ecuador) - M. L. Rosero Vallejo; O. A. Khlebosolova (Известия высших учебных заведений: Геология и разведка, 2024)
Background. The system of environmental monitoring in the Republic of Ecuador and its history is considered using the Galapagos Islands as an example. The need for its modification with the purpose of preventing the negative consequences of human activity is substantiated.Aim. To assess the environmental consequences of anthropogenic activity in the Galapagos Islands and to propose a unified environmental monitoring system for two protected natural areas of the Galapagos Islands.Materials and methods. The current laws and legislative acts related to the activity of the Republic of Ecuador state institutions in the field of environmental monitoring were analyzed. Statistical data and reports on monitoring programs in the Galapagos Islands were reviewed.Results. A unique environmental monitoring program for two protected natural areas of the Galapagos Islands was developed. It is recommended to complement the program with a system of stationary observations. This system is aimed at collecting data for assessing the impact of socioeconomic activity on the nature of the islands, monitoring the state of ecosystems, rare, endemic and invasive species, as well as for conducting scientific research to restore populations.